Mannitol mediates the mummification behavior of Thitarodes xiaojinensis larvae infected with Ophiocordyceps sinensis - Chai, Wenmin; Mao, Xianbing; Li, Chunfeng; Zhu, Liancai; He, Zongyi; Wang, Bochu (Frontiers in Microbiology, 2024)
Parasites can facilitate their own spread and reproduction by manipulating insect hosts behavior, as seen in the interaction between Thitarodes xiaojinensis and Ophiocordyceps sinensis. Infection by O. sinensis leads to the mummification of T. xiaojinensis larvae, but the underlying mechanisms remain mysterious. To uncover this parasitic relationship, metabolites were analyzed in infected and mummified larvae of T. xiaojinensis in this study. Significant changes were found in phenotype, fungal morphology in hemocoel, larval hardness, and mannitol metabolites in infected, mummified 0 h larvae and larvae 5 days after mummification behavior. Surprisingly, the occurrence of mummification behavior was accompanied by fungal dimorphism, as well as the absence of mannitol in both infected and non-infected larvae, until the initial accumulation of mannitol and the expression of mannitol-associated genes occurred at the time of mummification behavior. The presence of mannitol may promote fungal dimorphism to mediate changes in fungal toxicity or resistance, leading to the end of the fungus-insect coexistence period and the incidence of mummification behavior. Furthermore, mannitol injections increase the mummification rate of the infected larvae without significant difference from the normal mummification phenotype. This finding suggests the importance of mannitol in the mummification of host larvae infected with O. sinensis.